Intravenous catheter flanges as an external nasal stent: a novel technique - Nerurkar, Shibani A.; Iyer, Subramania; Krishnadas, Arjun; Subash, Pramod (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2024)
External nasal splints are commonly used for immobilization following nasal fracture reduction or rhinoplasty procedures. The literature documents the use of various materials like thermoplastic materials, aluminum, Orthoplast, fiberglass, plaster of Paris, and polyvinyl siloxane. These materials are bulky, time-consuming, expensive, and cumbersome to use, and have been associated with complications including contact dermatitis and epidermolysis. Furthermore, they cannot be retained if the situation warrants prolonged stabilization and immobilization. We introduce a new technique using readily available scalp vein catheter flanges as an external nasal stent. The technique is easy to master, inexpensive, and limits edema and ecchymosis, while stabilizing the reconstructed nasal skeleton in position during the healing period.